Techno-economic analysis of a pressure retarded osmosis (PRO) - seawater reverse osmosis (SWRO) hybrid: a case study - Ahmed, Amr; Alghamdi, Ahmed; Ahmed, Sultan (Frontiers in Energy Research, 2024)
This study offers a thorough techno-economic evaluation of a hybrid desalination system merging Pressure Retarded Osmosis (PRO) with Seawater Reverse Osmosis (SWRO) process. The primary aim is to determine the feasibility and economic viability of the hybridized approach to conventional SWRO methods. Diverse scenarios are studied based on parameters such as PRO module costs, energy savings achievable and payback period.Our findings reveal the potential for energy savings through the PRO-SWRO hybrid system. For instance, in scenarios where PRO membrane costs are low, such as $450 per element, and electricity prices are relatively high at $0.12 per kilowatt-hour, energy savings of up to 7% are attainable compared to standalone SWRO setups. This potential could be amplified with increasing salinity levels in the feed solution and higher draw solution pressures.The study extends beyond theoretical analysis, offering practical solutions for the design and implementation of sustainable desalination solutions; by studying the interaction between various parameters and their impact; on both energy consumption and economic viability.The current study estimates the membrane break-even costs of a PRO-SWRO hybrid system by estimating and equating the Net Present Value (NPV) of the SWRO system (base configuration) with the NPV of the PRO-SWRO hybrid. This research lays a solid foundation for the development of hybrid desalination systems capable of addressing water scarcity challenges in a cost-effective and environmentally sustainable manner.